METHOD OF TEACHING ENGLISH IN TECHNICAL SCHOOLS - Saminova Nodira Mukhtar qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: in this article the right methods of teaching English for students of technical schools. Specified teaching methods are mostly discussed in this article. We look  at  the  problem  connected  with  methods  of  teaching  English  to  international students  in  technical  schools  of  higher  education.  Our  research  is  focused  on  the solution of problems connected with teaching English in the field-specific terms to students in technical schools of higher education.